Typical absence seizures in adults: clinical, EEG, video-EEG findings and diagnostic/syndromic considerations. Issue 11 (November 1992) - Panayiotopoulos, C P; Chroni, E; Daskalopoulos, C; Baker, A; Rowlinson, S; Walsh, P
Abstract : Eighteen women and five men had typical absences. These included 10% of a consecutive hospital series of 200 adult patients with epileptic disorders. The absences began between the ages of seven and 46 years and varied in type and severity. Twenty patients also had generalised tonic-clonic seizures, ranging in frequency from one in a lifetime to one per month. Myoclonic jerks of the limbs occurred in 11 patients but were not associated with the absence attacks. Eyelid myoclonus consistently occurred with absence attacks in four patients and perioral myoclonus in two patients. Absence status occurred in five patients. Absence seizures were frequently unrecognised or misdiagnosed as complex partial seizures. Satisfactory control was achieved with sodium valproate. Electroencephalography, particularly video-electroencephalography, was invaluable in the diagnosis, but focal abnormalities in seven patients might have been erroneously interpreted as indicating partial seizures. This series showed that clinical and EEG manifestations are often syndrome-related and that there are more epileptic syndromes with typical absences than those presently recognised.